Strategi Guru Pendidikan Agama Islam (PAI) Dalam Mengatasi Kesulitan Membaca Al-Qur’an Kelas X di SMK Informatika Bina Generasi Ciomas Bogor - Rizki Mubarok (LPPM IAI Nasional Laa Roiba Bogor, 2023)
The ability to read the Qur'an for students is very important not only as a provision in the world, but also for provision in the hereafter. The success of a teacher in carrying out a learning task is largely determined by his understanding of what strategies, models and methods will be applied by a teacher. In the current era of globalization, there are many shifts in values ​​in people's lives because many of our generation are still unable to read the Qur'an properly and correctly, especially in understanding its meaning. Therefore, as a parent, you must try as early as possible to educate and familiarize your child with reading the Qur'an. The purpose of this research is to find out the strategy of Islamic religious education (PAI) teachers in overcoming difficulties in reading the Qur'an for class X at SMK Informatics Bina Generasi Ciomas Bogor. In this study the authors used a research method with a qualitative approach. The data used in this analysis is in the form of primary data obtained from interviews with PAI teachers and students of Ciomas Generations Bina Informatics Vocational School. The objects in this study were students of Informatics Vocational School of Generations Ciomas. The results of this study indicate that 1. The strategy of PAI teachers in overcoming difficulties in reading the Koran for students is by means of peer tutors, demonstrating reading the Koran, and adding hours outside of the subject. 2. The method used by PAI teachers in overcoming difficulties in reading the Qur'an for students is the lecture, rubiyat, and drill methods. 3. Factors that influence the difficulty of reading the Qur'an in students include the lack of interest and motivation from the students themselves, the attention and education factors of the students' parents, the influence of technology and the influence of the community environment. Keywords: Reading Al-Qur'an, Teacher, Strategy.